Comprehensive assessment of fertilization, spatial variability of soil chemical properties, and relationships among nutrients, apple yield and orchard age: A case study in Luochuan County, China. (March 2021) - Hou, Liyao; Liu, Zhanjun; Zhao, Jiarui; Ma, Pengyi; Xu, Xinpeng
Highlights: Apple-producing systems on China's Loess Plateau are overfertilized. Soil nutrients accumulated and slight acidification occurred in apple orchards. Apple yield was significantly correlated with exchangeable Ca. The optimal age for maximum apple yield was approximately 17 years. The most suitable sampling depth to evaluate fertility changes was 0–20 cm. Abstract: Data on fertilization and spatial characterization of soil chemical properties are crucial for developing sustainable apple production systems. However, such information at regional scale is scarce. We conducted a survey asking farmers in Luochuan County about their current use of fertilizers, and collected 290 soil samples from 0 to 20 cm and 20–40 cm depths, respectively, to examine the spatial variability of eight chemical properties, and analyze the possible relations between soil quality index (SQI), apple yield, and stand age. Results showed apple orchards were severely overfertilized, with chemical N-P2 O5 -K2 O fertilizers of 1230–795–1080 kg  ha −1  yr −1 and organic fertilizers applied at the rates of 74.7 kg N ha −1  yr −1, 66.1 kg P2 O5  ha −1  yr −1, and 75.8 kg K2 O ha −1  yr −1 . With the exception of pH, both coefficient of variation and variogram range showed a moderate to high variability (16.5–77.7%) and spatial dependency (7.10–47.8%) for selected parameters. Distribution maps illustrated that the 0–20 cm soil depth was characterized by typically higher soil nutrient contents compared with that of 20–40 cm depth. Relative to the data observed in the 1980s, the averaged pH values decreased by ~0.20 units across 0–40 cm depth, while soil organic matter, total N, available N, P, K and Zn, and exchangeable Ca (Ex-Ca) increased markedly (26.2–508%) in the 0–20 cm depth, whilst few changes ( 9.84–178%) occurred at 20–40 cm depth. Correlation analysis revealed that Ex-Ca was the unique variable that was significantly ( P  < 0.05) correlated with apple yield at 0–20 cm depth, suggesting the importance of soil Ex-Ca as an indicator of apple production. The relationship between apple yield and stand age was well described by a parabolic model, with ~17 years as the optimal stand age for producing the maximum apple yield. Notably, the SQI scores had significant relationships with apple yields for 8–13, 14–17 and 18–31-yr-old stands in the 0–20 cm depth, but the relationship was only significant for the 14–17-yr-old stands in the 20–40 cm depth, implying that 0–20 cm is the appropriate sampling depth for evaluating soil quality changes in apple production systems. Overall, long-term fertilization improved soil fertility of apple orchards, which required particular attention with regard to overuse of N, P and K fertilizers. Those results provide an important reference for China and other major apple-producing countries.